Perencanaan Instalasi Pengolahan Air Limbah Domestik di Kota X - Mohamad Rangga Sururi; Ramadhan, Gilang; Geovania Alves Belo; Ilma Azizah; Mila Dirgawati (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Rapid population growth in urban areas of Indonesia, particularly in satellite cities such as City X, has led to an increase in domestic wastewater generation. This condition causes negative impacts on the environment, especially on the quality of water bodies and public health. Limited land availability, uneven distribution of sanitation services, and fluctuations in pollutant loads are major challenges in domestic wastewater management. To address these issues, the construction of a Wastewater Treatment Plant (WWTP) is planned with characteristics of small land footprint, low operational costs, and the ability to accommodate fluctuating pollutant loads. The WWTP service area is planned to cover 591,514 m², with the projected population at the end of the planning period reaching 9.072 people in 2088. Wastewater entering the WWTP system has the following characteristics: BOD 162 mg/L, COD 268 mg/L, TSS 210 mg/L, ammonia 48,57 mg/L, and total coliform 22 × 10⁸ MPN/100 mL. The proposed treatment design alternatives include: a bar screen with dimensions of 2,4 m × 0,5 m × 0,5 m, grit chamber 13,5 m × 10 m × 1 m, grease trap 8,5 m × 2,82 m × 1,19 m, equalization tank 24 m × 24 m × 2 m, MBBR 20,57 m × 4,57 m × 4,57 m, and a disinfection unit 29,76 m × 1,25 m × 3 m. The treated wastewater is expected to comply with domestic wastewater quality standards in accordance with the Regulation of the Minister of Environment and Forestry No. 68 of 2016. The total land area required for this WWTP is 856,6 m².